1990
DOI: 10.2527/1990.68113694x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat sources and combinations on starter pig performance, nutrient digestibility and intestinal morphology.

Abstract: Three growth trials and one digestion trial were conducted to compare the effect of dietary fat sources and combinations on starter pig performance, nutrient digestibility and intestinal morphology. Growth trials 1 and 2, utilizing a total of 324 weanling pigs (21 +/- 3 d), were conducted to determine the influence of addition of soybean oil, coconut oil, choice white grease, 50% soybean oil: 50% coconut oil or 50% choice white grease: 50% coconut oil on starter pig performance. Diets were supplemented with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
8

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 9 publications
6
52
1
8
Order By: Relevance
“…It is possible that the added dietary fat affected digestibility of some amino acids by altering gastrointestinal structural and functional measurements. Li et al (1990) reported that intestinal villi were longer and rounder in weanling pigs fed a 50:50 combination of soybean oil:coconut oil versus the two fat sources individually. Also, Lindley et al (1995) found that improvements in absorptive function measured in vitro were induced in rats by feeding polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the added dietary fat affected digestibility of some amino acids by altering gastrointestinal structural and functional measurements. Li et al (1990) reported that intestinal villi were longer and rounder in weanling pigs fed a 50:50 combination of soybean oil:coconut oil versus the two fat sources individually. Also, Lindley et al (1995) found that improvements in absorptive function measured in vitro were induced in rats by feeding polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Jørgensen et al (1985) reported an increase of 1-2% in the ileal digestibility of CP, lysine and methionine, but not cystine and threonine, in growing pigs fed a diet containing 150 g fat kg -1 diet versus 30 g fat kg -1 diet. Li et al (1990) reported that CP digestibility was not affected by the addition of soybean oil, coconut oil, or a 50:50 combination to diets for weanling pigs. Imbeah and Sauer (1991) and Li and Sauer (1994) both noted improvements (up to 4.9%) in the ileal digestibility of some amino acids when canola oil was added to diets for growing and weanling pigs, respectively.…”
mentioning
confidence: 99%
“…The effect of fat type on the digestive utilisation of diets has been widely studied in swine and chickens (Li et al, 1990;Preston et al, 2001) but there is less information in rabbit. Almost all authors fi nd that dietary digestibility increases when fat is included in the diet (Xiccato, 1998;Bhatt and Swain, 2003;Cesari et al, 2009) and that a greater degree of non saturation of fatty acids (FA) in fat enhances the apparent digestibility of this fraction (Maertens et al, 1986;Santomá et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…O óleo de soja contém predominantemente ácidos graxos insaturados de cadeia longa, com uma relação insaturados/saturados (I/S) de 5,42; na gordura de coco predominam ácidos graxos saturados de cadeia média com uma relação (I/S) de 0,15 (Li et al, 1990).…”
Section: Introductionunclassified